Pre-service English teachers’ reticent beliefs towards oral participation in EAP classrooms - Soo, Ruey Shing; Goh, Hock Seng (Springer, 2017)
The purpose of this study was to investigate pre-service English teachers’ reticent beliefs towards oral participation in English for Academic Purpose classrooms. To this end, 144 Malaysian pre-service English teachers enrolled in a teacher-training programme participated as respondents in a survey conducted using the Reticent Belief Index. They were all diagnosed with high level of reticence prior to the study. In addition, 24 pre-service teachers, selected randomly from among the survey participants, took part in focus group discussions. The results of the study revealed that the majority of the pre-service English teachers subscribed to eight beliefs that are presumed to be associated with reticent behaviour. Additionally, a newly identified belief, ‘Kiasuim’ was also found to cause the pre-service teachers being reticent in the class. The results of the study point to the importance of alleviating pre-service teachers’ reticent behaviour via a remedial course which incorporates the elements of modifying reticent beliefs.